Pengaruh Debt To Equity Ratio, Return On Equity, Dan Earning Per Share Terhadap Return Saham Pada PT Sidomuncul Tbk Periode 2015-2024 - Shafa Zahra Muthi; Ani Meryati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the partial and simultaneous effects of Debt to Equity Ratio, Return On Equity, and Earning Per Share on Stock Returns at PT Sidomuncul Tbk, a company listed on the Indonesia Stock Exchange (IDX) for the period 2015-2024. The data analysis methods used in this study were descriptive statistical tests, classical assumption tests, multiple regression analysis, correlation coefficients, determination coefficients, T-tests, and F-tests. The results of the study show that the Debt to Equity Ratio partially has no effect on stock returns with a t-value of 1.049 < t-table 2.447 and a significance value of 0.335 > 0.05. Return on Equity also has no partial effect on stock returns with a t-value of 0.860 < t-table 2.447 and a significance value of 0.423 > 0.05. Meanwhile, Earning Per Share partially has a significant effect on stock returns with a t-value of 6.985 > t-table 2.447 and a significance value of 0.000 < 0.05. Meanwhile, the F test results show that Debt to Equity Ratio, Return on Equity, and Earning Per Share have a significant effect on Stock Return with a t-value of 16.344 > t-table 4.76 and a significance value of 0.003 < 0.05.